ENTREPRENEURIAL STRATEGY COMPASS AND ITS IMPACT ON ENTREPRENEURIAL BEHAVIORANALYTICAL RESEARCH IN THE MINISTRY OF FOREIGN AFFAIRS - Zayad Ali Abass (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2020)
The current research aims to test the impact of Entrepreneriual Strategy Compass onEntrepreneurial Behavior in the Ministry of Foreign Affairs, as well as to diagnose the ministry’s level of interest in research variables and their dimensions, to come up with a set of recommendations , Which contribute to improving its practice and adoption , and based on the novelty of the two variables and their urgent importance to the Ministry and its members on the one hand and society on the other hand ,The exploratory descriptive approach was adopted ,and it was applied in the environment of the Ministry of Foreign Affairs to form the research community for the diplomatic corps in the ministry , The research sample was intended to class it included (152) leaders (Ambassador, Minister Plenipotentiary, Adviser, First Secretary, Second Secretary, Third Secretary, Attaché), The main research tool was distributed to them to investigate opinions about the studied variables, (115) were retrieved from them, while the valid ones were for statistical analysis (112) views, data, data and limited interviews, while the research used statistical programs (AMOS V.25- SPSS V.26-SMART PLS V.3.3) to analyze the primary data, With the adoption of descriptive and inferential statistical methods represented in (normal distribution test, exploratory factor analysis, confirmatory factor analysis, validity and reliability test, arithmetic mean, standard deviation, relative difference coefficient, relative importance, Pearson correlation coefficient, simple linear regression coefficient, multiple regression coefficient ) To test research hypotheses , The statistical analysis revealed a number of results, the most prominent of which was the existence of a statistically significant effect of Entrepreneriual Strategy Compass onEntrepreneurial Behavior.